2000
DOI: 10.1108/13620430010371937
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence – a new evaluation for management development?

Abstract: Aims to explore whether emotional intelligence (EI) is a useful yardstick in measuring and understanding the``promotion readiness'' of middle managers in a global organisation. If the personal attributes and social abilities that reflect high emotional intelligence can be understood and assessed, then not only do we gain a new perspective on management development but steps can be taken to develop these activities to enhance people's potential. The article concludes with a glimpse into the future and how EI ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 4 publications
1
33
0
1
Order By: Relevance
“…Past research supporting the proposition that ingratiatory behaviour leads to substantial advancement (Hypothesis 5) has been extensive (see Gordon (1996), Kristof-Brown (2000) and Westphal and Stern (2006) for information on relevant studies) and is corroborated by the present investigation. Previous research in the field of EI has repeatedly concluded that high EI is associated with relatively rapid promotion to the top echelons of organizations (see Carmeli, 2003;Dulewicz and Higgs, 1999;Langley, 2000). The acceptance of Hypothesis 6 is fully compatible with these prior studies.…”
Section: Reaching the Board 45supporting
confidence: 67%
“…Past research supporting the proposition that ingratiatory behaviour leads to substantial advancement (Hypothesis 5) has been extensive (see Gordon (1996), Kristof-Brown (2000) and Westphal and Stern (2006) for information on relevant studies) and is corroborated by the present investigation. Previous research in the field of EI has repeatedly concluded that high EI is associated with relatively rapid promotion to the top echelons of organizations (see Carmeli, 2003;Dulewicz and Higgs, 1999;Langley, 2000). The acceptance of Hypothesis 6 is fully compatible with these prior studies.…”
Section: Reaching the Board 45supporting
confidence: 67%
“…To ensure continued organisational performance and to maintain the competitive advantage, organisations must therefore constantly implement changes in strategy, structure, process and culture (Higgs, 2002;Langley, 2000). Goleman (1998) proposes a solution of self-awareness as a key skill in handling stress, thereby indicating that a lack of emotional intelligence in such an unstable environment means possible failure that can impact on everyone's future.…”
mentioning
confidence: 99%
“…The authors noted that successful leaders utilize those traits to connect with others to inspire, motivate and challenge them [35,36]. Langley compared senior managers with middle managers targeted for promotion and found that senior managers exhibited significantly higher levels of emotional intelligence traits, supporting the notion that emotional intelligence was an important tool for measuring promotional readiness [37]. Further, Dulewicz and Higgs concluded in a seven-year longitudinal study that emotional intelligence was significantly more important that intellect in the advancement of managers [38].…”
Section: Relevant Emotional Intelligence Researchmentioning
confidence: 94%